2022
DOI: 10.1177/00332941221100451
|View full text |Cite
|
Sign up to set email alerts
|

Social and Psychological Effects of COVID-19 Pandemic on Adolescents’ and Young Adults’ Mental Health: A Cross-Cultural Mediation Study

Abstract: The ongoing pandemic has dramatically disrupted daily life, increasing the risk of developing psychiatric disorders and poor mental wellbeing. The compound effects of social, political and psychological stressors have increased psychological symptoms among adolescents and young people, with worries about COVID-19 playing a central role in the clinical course of their mental health problems caused by the pandemic. The aim of this cross-cultural study was to examine the social psychological effects of COVID-19 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…At the same time, they were more likely to express a desire for a happy life in the future. This seems plausible in light of recent research indicating lower life satisfaction among female respondents [65,68,86]. Female respondents were more likely to report health-related concerns about the future.…”
Section: Differences According To Gendermentioning
confidence: 76%
“…At the same time, they were more likely to express a desire for a happy life in the future. This seems plausible in light of recent research indicating lower life satisfaction among female respondents [65,68,86]. Female respondents were more likely to report health-related concerns about the future.…”
Section: Differences According To Gendermentioning
confidence: 76%
“…By international comparison, Sweden has had less lock-down and restrictions and there might be cultural differences in how much the pandemic affects adolescents [ 51 ], which limits comparisons between countries. The lives of high-school students in Sweden have, however, been affected with distance education.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional clinical psychologists have studied MHPs in adolescents from a pathological perspective, focusing on mental illness, general mental health disorders, emotional and behavioral problems, psychological distress, and disease symptoms ( 23 ). Studies have shown that individuals' mental health is related to their social-ecological environment, family education, and individual psychological traits; for example, the on-going COVID-19 epidemic has increased the risk of MHPs in adolescents and has impacted their emotional state and subjective well-being ( 24 ). Being a member of a family with a low economic status has a significant positive predictive effect on an individual's MHPs ( 25 ).…”
Section: Introductionmentioning
confidence: 99%